2018
DOI: 10.4103/1319-2442.239654
|View full text |Cite
|
Sign up to set email alerts
|

The impact of blood flow rate on dialysis dose and phosphate removal in hemodialysis patients

Abstract: The inadequacy of dialysis and hyperphosphatemia are both associated with morbidity and mortality in chronic hemodialysis (HD) patients. Blood flow rate (BFR) during HD is one of the important determinants of increasing dialysis dose. The aim of this study was to determine the effect of increasing BFR on dialysis dose and phosphate removal. Forty-four patients were included in a cross-sectional study. Each patient received six consecutive dialysis sessions as follows: three consecutive sessions with a BFR of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Wang et al demonstrated that anuric patients undergoing peritoneal dialysis had elevated serum P levels nearly twice as often as patients without residual renal function 28 . The removal of P with dialysis varies considerably and is affected by blood flow, dialysis duration, the predialysis serum P, PTH level and ultrafiltration volume 29,30 . Traditional thrice weekly hemodialysis leads to a rebound of serum P from extracellular stores, including bone, after dialysis but the timing of that rebound varies [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al demonstrated that anuric patients undergoing peritoneal dialysis had elevated serum P levels nearly twice as often as patients without residual renal function 28 . The removal of P with dialysis varies considerably and is affected by blood flow, dialysis duration, the predialysis serum P, PTH level and ultrafiltration volume 29,30 . Traditional thrice weekly hemodialysis leads to a rebound of serum P from extracellular stores, including bone, after dialysis but the timing of that rebound varies [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…The European Best Practice Guidelines, Kidney Disease Outcomes Quality Initiative (KDOQI) and the Indonesian Nephrology Association (PERNEFRI) recommend a URR of at least 65%. 6,8,9 In patients with end stage renal disease (ESRD), AVF is the preferred access to HD, but often complicated by stenosis. Stenosis in AVF dysfunction can be managed with endovascular procedures such as percutaneous balloon venoplasty.…”
Section: Introductionmentioning
confidence: 99%